Can bedside patient-reported numbness predict postoperative ambulation ability for total knee arthroplasty patients with nerve block catheters? - Mudumbai, Seshadri C. (Korean J Anesthesiol, 2016)
BACKGROUND: Adductor canal catheters offer advantages over femoral nerve catheters for knee replacement patients because they produce less quadriceps muscle weakness; however, applying adductor canal catheters in bedside clinical practice remains challenging. There is currently no patient-reported outcome that accurately predicts patients' physical function after knee replacement. The present study evaluates the validity of a relatively new patient-reported outcome, i.e., a numbness score obtained using a numeric rating scale, and assesses its predictive value on postoperative ambulation. METHODS: We conducted a retrospective cohort study pooling data from two previously-published clinical trials using identical research methodologies. Both studies recruited patients undergoing knee replacement; one studied adductor canal catheters while the other studied femoral nerve catheters. Our primary outcome was patient-reported numbness scores on postoperative day 1. We also examined postoperative day 1 ambulation distance and its association with postoperative numbness using linear regression, adjusting for age, body mass index, and physical status. RESULTS: Data from 94 subjects were included (femoral subjects, n = 46; adductor canal subjects, n = 48). Adductor canal patients reported decreased numbness (median [10(th)–90(th) percentiles]) compared to femoral patients (0 [0–5] vs. 4 [0–10], P = 0.001). Adductor canal patients also ambulated seven times further on postoperative day 1 relative to femoral patients. There was a significant association between postoperative day 1 total ambulation distance and numbness (Beta = –2.6; 95% CI: –4.5, –0.8, P = 0.01) with R(2) = 0.1. CONCLUSIONS: Adductor canal catheters facilitate improved early ambulation and produce less patient-reported numbness after knee replacement, but the correlation between these two variables is weak.